The Characteristics of Coconut Oil Products Based on Papaya Juice and Duration Fermentation using Rhizopus sp. - Sari Sekar Ningrum; Aidha Zulaika (Universitas Panji Sakti, 2022)
Coconut oil is a basic human need. Coconut oil can be made both traditional and enzymatically. Enzymatic manufacture of coconut oil is the separation of oil in coconut milk using protein-breaking enzymes called proteolytic enzymes. Enzymatic production of coconut oil has the advantages of easy-to-obtain raw materials, does not require much energy, and simple processing. This study was conducted to determine the effect of time and amount of papaya juice used with the coconut oil yields obtained. The results of the study at a time of 3 days with a volume of 75 ml of papaya juice, it was obtained that the volume of coconut oil was the most, which was 11.4 ml. Making coconut oil using coconut milk and papaya juice mixed and added 2 grams of tempeh yeast then measured the pH to pH 4. Next, the glass is closed so that air does not enter during the fermentation time of 3-5 days. After being fermented then separated between water and pulp from making coconut oil. Next, pulp from making coconut oil is heated to produce oil. In addition, the free fatty acid test and the saponification number test were also carried out to determine whether the coconut oil produced complies with the quality requirements of SNI 2902-2011. This indicates that some treatment effect of coconut oil compiles is possible, a quality requirement of SNI 2902-2011.